Molecular identification, characterization, and antagonistic activity profiling of Bacillus cereus LOCK 1002 along with the in-silico analysis of its presumptive bacteriocins - Islam, Samarth; Farjana, Mithila; Uddin, Muhammad Ramiz; Akter, Sharmin; Jabin, Anika; Nafisa, Hazika Tuz Zohura; Siraji, Siam; Morshed, A K M Helal; Rimti, Fahmida Hoque; Naim, Zannatul; Sakib, Mohiuddin; Sarker, Pallab; et al. (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This research aimed to isolate, identify, and characterize a new strain of Bacillus cereus through different molecular biology approaches so that it could be further studied for therapeutic purposes against selective enteric pathogens. Materials and Methods: Pure isolates of B. cereus were prepared from buffalo yogurt samples in REMBA medium. Initially, the morphological, physiological, and biochemical properties were studied accordingly. Following the tests, the molecular identification for the strain identification was conducted through plasmid DNA extraction, PCR, agarose gel electrophoresis, and 16S rRNA sequencing up to 1.37 kb. Afterward, the antibiotic sensitivity [Epsilometer test (E-Test)] and antifungal activity were tested considering different concentrations. Being classified from the aforementioned tests, a comprehensive antimicrobial activity test was conducted using the cell-free-supernatant (CFS) of the test strain against selective enteric pathogens in humans in vitro. Besides, the different clusters of genes were identified and characterized for understanding the presumptive bacteriocins present in the CFS of the strain in silico, where molecular string properties were calculated. Finally, the evolutionary relationship among diversified bacteriocins synthesized by different Bacillus strains was studied to predict the CFS-containing bacteriocins of the new strain. Results: Purified isolates of B. cereus were Gram-positive rods and showed significant tolerance (p < 0.0001) to different concentrations of pH, phenol, bile salt, and NaCl. 16S rRNA revealed the strain as LOCK 1002, which was strongly sensitive to all the antibiotics used and resistant to selective antifungal agents. The CFS of B. cereus LOCK 1002 was found to be a very promising antagonist to all the enteric pathogens used in the culture condition. Two gene clusters were predicted to be interconnected and responsible for different presumptive bacteriocins. Conclusion: The newly identified LOCK 1002 can be a very potent strain of B. cereus in use as an antimicrobial agent for having different bacteriocin coding gene clusters. J. Adv. Vet. Anim. Res., 9(4): 663–675, December 2022 http://doi.org/10.5455/javar.2022.i635